THE STUDENTS' VALUE-BASED CHOICES AND ATTITUDES - A SUPPORT FOR THEIR SOCIAL AND PROFESSIONAL INVOLVEMENT? - Elena NEDELCU; Mihai NEDELCU (Challenges of the Knowledge Society, 2016)
In social sciences, values are used to define individuals, smaller or larger groups and societies. Values directly hint at what we are and they determine our action. The first part of the paper defines the basic concepts we use in the paper. There is a brief presentation of the polemics regarding the definition of values, norms and attitudes, as well as of the outcome of the research work carried out for identifying the young people's value-based choices in the present Romanian society. In the second part of the paper we analyze the main data resulted from the social inquiry that we pursued on the basis of the survey that we applied and of the focus-group that we considered. The survey was meant to draw up a hierarchy of the students' values, see “the 21 values list”. The focus-group had the role of debating certain preliminary outcomes of the research, and later on, of indicating analysis directions for interpreting the collected data. The present study is the first stage of a larger research work that aims at identifying the extent to which students are oriented towards values which support social and professional success in the present Romanian society.